Dual-band, wide-angle, and high-capture efficiency metasurface for electromagnetic energy harvesting - Al Gburi, Ahmed Jamal Abdullah; Zakaria, Zahriladha; Ahmed Ghaleb Amer, Abdulrahman; Othman, Nurmiza; Sapuan, Syarfa Zahirah; Alphones, Arokiaswami; Hassan, Mohd Fahrul (MDPI, 2023)
A dual-band metasurface (MS) with a wide reception angle operating at Wi-Fi bands(2.4 GHz and 5.4 GHz) is presented for electromagnetic (EM) energy harvesting applications. The MS unit cell comprises a subwavelength circular split ring resonator printed on the low-loss substrate. An air layer is sandwiched between two low-loss substrates to enhance the harvesting efficiency at operating frequencies. One of the main advantages of the proposed MS is that it uses only one harvesting port (via) to channel the captured power to the optimized load (50 Ω), which simplifies the design of a combined power network. According to the results of full-wave EM simulations, the proposed MS has a near-unity efficiency of 97% and 94% at 2.4 GHz and 5.4 GHz, respectively, for capturing the power of incident EM waves with normal incidence. Furthermore, the proposed MS harvester achieves good performance at up to 60◦ oblique incidence. To validate simulations, the MS harvester with 5 × 5-unit cells is fabricated and tested, and its EM properties are measured, showing good agreement with the simulation results. Because of its high efficiency, the proposed MS harvester is suitable for use in various microwave applications, such as energy harvesting and wireless power transfer